Innovative research and practices in second language acquisition and bilingualism - Schwieter, John W. (Language learning and language teaching., 2013)
In developing this summary and commentary, I have chosen to highlight the connections the authors make to the practice of instructed second language acquisition and their rationale. To that end, I have classified the pedagogical applications, implications and extrapolations offered by the authors into three categories. First, we find suggestions for particular types of instructional materials, activity sequences, and/or approaches to instruction. Second, we find recommendations for curricular changes and language programs in terms of the timing, sequencing and/or the content of instruction. La.